GREEN CHEMISTRY IN SCIENTIFIC LITERATURE a bibliometric study and research trends. - Sharma, Sanjay K.; DEMIR, HASAN ([S.l.] : CRC PRESS, 2019)
The study covers recent statistical data of the principles of Green Chemistry, a bibliometric study of research and review papers published between 1999 and 2018, and recent trends of research topics on Green Chemistry. This study collects, processes and refines available information in scientific area. The authors have provided recent statistical data on the principles of Green Chemistry and a bibliometric analysis of published review and research articles, as well as trends of research topics, in this unique volume. Key Features: Provides a comprehensive review of recent statistical data on the principles of Green Chemistry. Presents a bibliometric analysis of published reviews and research articles as well as the trends of research topics in Green Chemistry. Surveys and critically analyzes Green Chemistry literature The subject matter is timely since tracking of research trends in the Green Chemistry field is important for directing future research
OCLC-licensed vendor bibliographic record.
Keywords: Green chemistry -- Research; SCIENCE / Chemistry / Organic; TECHNOLOGY / Engineering / Chemical & Biochemical